SIKAP MAHASISWA MEMANFAATKAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBELAJARAN TERBUKA DAN JARAK JAUH - Farida, Idha; Yuliana, Ernik (LPPM Universitas Terbuka, 2014)
Utilization of information and communication technology (ICT) in open and distance education is very important. Universitas Terbuka (UT-The Indonesia Open University) gradually began developing and using ICT applications for a variety of purposes, both academic and administrative. In the academic services, UT provides learning materials specifically designed for independent learning. The students can using learning materials provided by UT through the internet such as online tutorial (tuton), web supplement, internet television (I-TV), and online exercise independent (LM-Online). The objectives of the research were: (i) to describe students attitude for using information and communication technology in open and distance learning, and (ii) to describe the relationship between the students characteristics with their attitude for using information and communication technology in open and distance learning. This research was conducted with the survey methods and observations in the Regional Office (UPBJJ-UT) in Serang dan Bengkulu. The 52 students samples were randomly selected as respondents. The data were analyzed through Spearman rank correlation test. The result showed students attitude for using information and communication technology in open and distance learning is pretty good. The result showed educational students background were significantly correlated with their attitude for using web supplement and I-TV. A student region of residence were significantly correlated with their attitude for using I-TV. There was also a significant correlation between the availability of internet facilities and computer ownership with their attitudes for using tuton, web supplement and I-TV. Pemanfaatan teknologi informasi dan komunikasi ( TIK ) dalam pendidikan terbuka dan jarak jauh sangat penting. Universitas Terbuka (UT) secara bertahap mulai mengembangkan dan menggunakan aplikasi ICT untuk berbagai keperluan, baik akademik dan administratif. Dalam pelayanan akademik, UT menyediakan bahan ajar yang dirancang khusus untuk belajar mandiri. Para mahasiswa dapat menggunakan bahan pembelajaran yang diberikan oleh UT melalui internet seperti tutorial secara online (Tuton), suplemen web , televisi internet (I- TV), dan latihan mandiri online (LM - Online). Tujuan dari penelitian ini adalah: (1) untuk menggambarkan sikap mahasiswa untuk menggunakan teknologi informasi dan komunikasi dalam pembelajaran terbuka dan jarak jauh, dan (2) untuk menggambarkan hubungan antara karakteristik mahasiswa dengan sikap mereka dalam menggunakan teknologi informasi dan komunikasi pada media pembelajaran terbuka dan jarak jauh. Penelitian ini dilakukan dengan metode survei dan pengamatan di Kantor Wilayah (UPBJJ-UT) di Serang dan Bengkulu. Sampel sebanyak 52 mahasiswa dipilih secara acak sebagai responden. Data dianalisis melalui uji korelasi Rank Spearman. Hasil penelitian menunjukkan sikap mahasiswa menggunakan teknologi informasi dan komunikasi dalam pembelajaran terbuka dan jarak cukup bagus. Selanjutnya hasil penelitian menunjukkan latar belakang pendidikan mahasiswa secara signifikan berkorelasi dengan sikap mereka untuk menggunakan suplemen web dan I-TV. Tempat tinggal mahasiswa secara signifikan berkorelasi dengan sikap mereka untuk menggunakan I- TV. Ada juga hubungan yang signifikan antara ketersediaan fasilitas internet dan kepemilikan komputer dengan sikap mereka untuk menggunakan Tuton , suplemen web dan I- TV .